Optical aptasensor for in situ detection and quantification of methylxanthines in Ilex guayusa - Briggitte Alexandra León Intriago; Andre Cristina Montero Oleas; Diana Sofía Mollocana Yánez; Diana Joella Calderón Carvajal; María de Lourdes Torres Proaño (ACI Avances en Ciencias e Ingenierías, 2022)
The present work pursued the development of a system to detect and quantify methylxanthines in Ilex guayusa. The system, called IPMA (In situ Plant Metabolite Aptasensor), is based on an optical aptasensor that integrates a DNA complex and a porphyrin (NMM IX). IPMA's ability to detect known amounts of theophylline and caffeine in solution and infiltrated in guayusa's leaves was evaluated. The detection limits determined were: 0.25 mM for theophylline in solution, 0.1 mM for caffeine in solution, and 130 mM for caffeine in I. guayusa leaves. These results demonstrate the potential of IPMA to detect and quantify metabolites of interest directly from biological samples. Developing this type of tool will provide a wide range of applications such as the in situ determination of physiological stress in plants and the characterization of plant varieties with a higher content of compounds of pharmaceutical or food interest.